Impact of Vertical Vibration on Group Piles During Earthquake Loading: Experimental Findings - Noman, Bilal J.; Albusoda, Bushra S. (Civil Engineering Journal, 2024)
This study presents novel research on the impact of vertical vibration on the dynamic response of pile groups embedded in stratified soil under seismic loading conditions. An experimental setup was employed wherein the piled machine foundation was subjected to vertical vibrations at three operating frequencies (10, 20, and 30 Hz) and subsequently exposed to four levels of seismic acceleration (0.1 g, 0.34 g, 0.77 g, and 0.82 g). Piles with a length-to-diameter ratio of 25 were embedded in a stratified soil profile, with an upper loose layer (30% relative density) and a lower dense layer (80% relative density) acting as end-bearing. Measurements and analyses of horizontal and vertical accelerations, and amplification factors were conducted using the Fast Fourier Transform (FFT), spectral acceleration (Sa), and variation of acceleration with depth. The results demonstrated a significant reduction in horizontal acceleration, with a peak ground acceleration (PGA) reduction of up to 64% in average, particularly at higher frequencies such as 30 Hz. The mitigation efficiency at 30Hz improved with increasing PGA, showing reductions of 42, 68, 75, and 63% for seismic accelerations of 0.1 g, 0.34 g, 0.77 g, and 0.82 g, respectively. The analysis further revealed harmonic resonance and higher mode effects at lower frequencies, with nonlinear soil behavior affecting the resonance and amplification patterns. Additionally, the results demonstrate that the far-field accelerations exceeded the near-field accelerations within the pile group, particularly in the surface layer. The results indicated that the initial vibration amplitudes exceeded the safe operating limits outlined in ACI 351.3R-18 under seismic loading, particularly at higher seismic acceleration levels and lower frequencies. Additional modified charts were presented to account for these conditions. The results presented promising evidence for using vertical vibrations as an earthquake-mitigation strategy. However, avoiding operating at frequencies less than 10 Hz is recommended because of the potential resonance and interaction with horizontal accelerations during earthquakes. Doi: 10.28991/CEJ-SP2024-010-010 Full Text: PDF